Pengenalan Teknologi Hilirisasi Dadiah Berbasis Kearifan Lokal - Dewi, Kurnia Harlina; Yenrina, Rina; Rahayu, Lisa; Morita, Rina; Yanti (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
One of the products processed by Nagari Aia Dingin is Dadiah. Dadiah is a traditional food of the Minangkabau tribe, a fermented buffalo milk product that requires development to be able to compete in the global era. The implementation method is carried out through the delivery of material and discussions using broadcasts that are easy to understand and interesting for activity participants. Results of PkM activities introducing Dadiah downstream products. This can be seen from the results of participants' knowledge of dadiah processing technology, 1.10 to 1.33 (don't know). After the PkM activities in developing traditional food, participants stated that they knew enough but still did not know much about the technology for processing Ampiang Dadiah Kriuk (2.00). All participants stated that at the beginning of the activity, the difficulty level of Dadiah-based processing was difficult (3.71), but after participating in the PkM activity, participants assessed that the technology for processing Dadiah downstream products was not difficult (1.48).